The Development of “Manabu Bunpou” Smartphone Application for Basic Japanese Grammar Learning - Herniwati, Herniwati; Haristiani, Nuria; Judiasri, Melia Dewi; Rabathi, Millati Qisti; Funaki, Noa (Universitas Pendidikan Indonesia (Indonesia University of Education), 2024)
One of the difficulties students experience in learning Japanese grammar is limited study time. Practical learning without limitations of space, time, and place through an e-learning system allows students to learn independently, efficiently, and effectively which also can be applied as a solution to improve students' mastery of Japanese grammar. This research applies the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model in developing e-learning application designs on smartphones. The data in this study were collected using pre-experimental methods and by distributing Likert scale questionnaires to fifteen students. The application developed is named “Manabu Bunpou”, validated by the IT team, and consists of JLPT level N4 grammar practice tests, several levels, and quizzes. The material including ninety-three Japanese sentence patterns developed from several sources and also contains conversation videos accompanied by texts. From the questionnaires distributed to Japanese language learners, the “Manabu Bunpou” application is considered highly accessible, helps improve understanding of basic Japanese grammar, and supports independent learning. However, according to the participants, the materials in the application are still limited and hence need further development.